Penerapan Energi Terbarukan sebagai Sumber Energi Masyarakat Nelayan Lam Awe Aceh Besar - Suhaeri; Zulfadhli; Bachtiar, Dandi; Ali, Nurdin; Arhami; Pradinata, Edy; Alfisyahrin; Syukriyadin; Syukri , Mahdi (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2024)
This report describes efforts to implement renewable energy technologies as a solution to meet the energy needs of the fishing community in Lam Awe, Aceh Besar. A community engagement approach was used to integrate renewable energy technologies into the daily lives of the fishing community. The study includes the process of identifying community needs, selecting appropriate technologies, and implementing renewable energy solutions. Research methods included participatory surveys, training sessions, and mentoring to ensure active participation and deep understanding from the local community. The results indicate that the implementation of renewable energy can enhance energy access, reduce operational costs, and support environmental sustainability in coastal areas. This report contributes to the context of sustainable technology application for fishing communities, highlighting the importance of collaboration between academics, practitioners, and communities in developing sustainable energy solutions.